Women’s intuition as attunement: a biological and social perspective - Verma, Shalini; Kind, Lucy (Raiya) (Frontiers in Sociology, 2025)
This paper proposes that women, due to both evolutionary pressures and sociocultural reinforcement, have developed heightened intuitive capacities, more specifically, attunement capabilities. We define attunement as the ability to somatically, emotionally, and cognitively resonate with the internal states of oneself or another. It is especially important in contexts involving caregiving, safety detection, and emotion regulation. Crucially, this ability is not static; it can be dulled or distorted by traumatic experience and reclaimed through healing. Through the restoration of nervous system balance, individuals, and especially trauma survivors, may gain more accurate and deeper information and thus greater access to their intuition. By grounding female intuition in the body and relational experience, we position it as a vital, learnable, and reparative human skill, particularly important in—but not limited to—caregiving, therapy, decision making, and community life. Finally, we stress that since attunement is an ability innate to all humans and not just women, men too can heighten their attunement abilities, and thus their intuition, and we as a society can encourage all beings to increase this potent and beneficial ability.